2011
DOI: 10.1128/aac.00832-10
|View full text |Cite
|
Sign up to set email alerts
|

Human Pharmacokinetics and Safety Profile of Finafloxacin, a New Fluoroquinolone Antibiotic, in Healthy Volunteers

Abstract: Finafloxacin is a new fluoroquinolone antibiotic with the unique property of increasing antibacterial activity at pH values lower than neutral. Whereas its antibacterial activity at neutral pH matches that of other quinolones in clinical use, it is expected to surpass this activity in tissues and body fluids acidified by the infection or inflammation processes. Pharmacokinetic parameters of oral single and multiple doses of up to 800 mg of finafloxacin and safety/tolerability observations were assessed in a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 7 publications
(5 reference statements)
2
29
0
Order By: Relevance
“…anaerobiosis [5], in artificial and human urine [2,6] and in artificial and cystic fibrosis sputum [7] and it is also active against biofilms of bacterial cells and other quiescent forms of growth [8]. In addition, finafloxacin has demonstrated an excellent, high-dose-enabling safety profile both in preclinical and clinical studies, showing no indications of the cardiac or other toxic effects observed for other members of its class [9].…”
Section: Introductionmentioning
confidence: 98%
“…anaerobiosis [5], in artificial and human urine [2,6] and in artificial and cystic fibrosis sputum [7] and it is also active against biofilms of bacterial cells and other quiescent forms of growth [8]. In addition, finafloxacin has demonstrated an excellent, high-dose-enabling safety profile both in preclinical and clinical studies, showing no indications of the cardiac or other toxic effects observed for other members of its class [9].…”
Section: Introductionmentioning
confidence: 98%
“…Finafloxacin, an investigational fluoroquinolone suitable for intravenous and oral administration, is being developed as sequential therapy for bacterial infections, including the treatment of UTIs (9). This compound exhibits essential features required to successfully treat such infections: good activity against Gram-positive, Gram-negative, and anaerobic pathogens with a bactericidal mechanism of action (4); a high level of excretion in the urine (10,11); and increased potency at acidic pH (4,5). Fluoroquinolones inhibit the activity of bacterial type II topoisomerases, i.e., DNA gyrase and topoisomerase IV.…”
mentioning
confidence: 99%
“…The level of urinary excretion of finafloxacin is high (47), and its activity is impaired neither by an acidic pH nor by high concentrations of divalent cations, which prevail in UTIs (4850). In contrast, the activities of expanded-spectrum fluoroquinolones are diminished under such growth conditions (48, 49).…”
Section: Introductionmentioning
confidence: 99%